Basal Cell Carcinoma Arising from Xeroderma Pigmentosum: A Case Report and an Immunohistochemical Study - Sadanori Furudate; Taku Fujimura; Gen-ichi Tojo; Takahiro Haga; Setsuya Aiba (Karger Publishers, 2013)
We describe a 26-year-old Japanese patient with basal cell carcinoma arising from xeroderma pigmentosum (XP). Immunohistochemical staining revealed dense infiltration of CD163+ M2 macrophages, together with Foxp3+ regulatory T cells. Interestingly, MMP9, which was reported as one of the functional markers for immunosuppressive macrophages, was al-so detected in the CD163+ M2 macrophage-infiltrated areas. Our case suggests the immunological background of tumor development in a patient with XP.